Sprachgeschichte und Medizingeschichte: Texte - Termini - Interpretationen - Riecke, Jörg (Lingua Historica Germanica, 2017)
"Medieval and early modern medical treatises are a major source for understanding how people wrote about the body, illness, and healing during different phases of European linguistic and cultural history. Research on the landscape of older medical works also relates to the present, by developing historical comparisons between historical medical concepts and their expression and today's perspectives and terminology"--